Unveiling the Hidden Causes: Identifying the Drivers of Human–Elephant Conflict in Nilgiri Biosphere Reserve, Western Ghats, Southern India - Nagarajan Baskaran; Selvarasu Sathishkumar; Varadharajan Vanitha; Mani Arjun; Perumal Keerthi; Nikshepan Goud Bandhala (Animals)
Since the human population is growing beyond the earth’s ability to sustain it, more people are being brought into contact with wildlife, leading to increasing human–wildlife conflict. The Asian elephant, a wide-ranging megaherbivore, is being increasingly threatened by human–elephant conflict [HEC]. Its conservation depends on identifying the causes of HEC and implement measure to mitigate the HEC effectively. We studied the drivers of HEC among five forest divisions in Western Ghats, India, that support a high density of elephants across Asia. Comparing the last six years’ data on HEC with 26 ecological covariates in the GLMM framework, we identified spatiotemporal variations and drivers of crop, and property damages and human casualties. Spatially, HEC was highest in the territorial division and lowest in those declared as Protected Areas earlier. The comparison of crop damage with covariates showed that crop damage decreased with the grass biomass index, elephant density, extent of dry-thorn, and deciduous habitats, and forest range area, while it increased with adult male % and forest range perimeter. Similarly, the property damage by elephants increased with crop damage frequency and human settlement/cultivation area, but decreased with grass biomass, forest range area, and deciduous habitat area. Human casualties due to elephants increased with property damage, ambient temperature, and forest range perimeter, but decreased with grass biomass. Overall, the decrease in HEC with grass biomass, and the increase in HEC with human settlement and forest range perimeter indicate that anthropogenic pressure that decreases the grass biomass and degrades the habitat is the likely root cause of HEC, and minimizing it would reduce overall HEC.